2019
DOI: 10.1002/ptr.6530
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of EGFR and MET by Echinatin retards cell growth and induces apoptosis of lung cancer cells sensitive or resistant to gefitinib

Abstract: Patients with non-small-cell lung cancer (NSCLC) containing epidermal growth factor receptor (EGFR) amplification or sensitive mutations initially respond to tyrosine kinase inhibitor gefitinib; however, the treatment is less effective over time. Gefitinib resistance mechanisms include MET gene amplification. A therapeutic strategy targeting MET as well as EGFR can overcome resistance to gefitinib. In the present study we identified Echinatin (Ecn), a characteristic chalcone in licorice, which inhibited both E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…By screening the antiviral effects of 389 monomer compounds in the “three formulas and three medicines” (TargetMol, L6720, Supplementary Table S1 ) at the final concentration of 50 μM, six of the monomer compounds have been found to reduce the GX_P2V infection remarkably ( Figure 2A , Supplementary Figure S1 and Supplementary Table S2 ) . Among these six drugs, high concentrations of two anticancer drugs including echinatin ( Oh et al., 2020 ) (EC 50 = 20.89 µM, CC 50 = 120.1 µM, SI = 5.75), and licochalcone B ( Song et al., 2020 ) (EC 50 = 24.90 µM, CC 50 = 106.5 µM, SI = 4.28) were required to inhibit the viral infection ( Figure 2B ) . Notably, andrographolide ( Enmozhi et al., 2020 ) (EC 50 = 6.786 µM, CC 50 = 95.73 µM, SI = 14.11) were also found to block the virus infection ( Figure 2B ) .…”
Section: Resultsmentioning
confidence: 99%
“…By screening the antiviral effects of 389 monomer compounds in the “three formulas and three medicines” (TargetMol, L6720, Supplementary Table S1 ) at the final concentration of 50 μM, six of the monomer compounds have been found to reduce the GX_P2V infection remarkably ( Figure 2A , Supplementary Figure S1 and Supplementary Table S2 ) . Among these six drugs, high concentrations of two anticancer drugs including echinatin ( Oh et al., 2020 ) (EC 50 = 20.89 µM, CC 50 = 120.1 µM, SI = 5.75), and licochalcone B ( Song et al., 2020 ) (EC 50 = 24.90 µM, CC 50 = 106.5 µM, SI = 4.28) were required to inhibit the viral infection ( Figure 2B ) . Notably, andrographolide ( Enmozhi et al., 2020 ) (EC 50 = 6.786 µM, CC 50 = 95.73 µM, SI = 14.11) were also found to block the virus infection ( Figure 2B ) .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the ability to induce the intrinsic pathway of apoptosis has also been described in several natural chacones such as echinatin [ 73 ], broussochalcone [ 74 ], hydroxysafflor yellow A [ 75 ], 3-deoxysappanchalcone [ 76 ], sappanchalcone [ 77 ], and many others (see also Table 1 ).…”
Section: Induction Of Cell Deathmentioning
confidence: 99%
“…15 Studies have shown that Ech has a wide range of biological properties, including anti-inflammatory and anti-tumor effects. 16 Importantly, Liang et al 17 confirmed that Ech may undergo electron transfer and proton transfer to cause antioxidant effects. However, to date, the effects of Ech on oxidative stress-induced LEC damage have not been reported, and its molecular mechanism is largely unclear.…”
Section: Introductionmentioning
confidence: 99%